2019
DOI: 10.2174/1574893614666190409110843
|View full text |Cite
|
Sign up to set email alerts
|

HS-MMGKG: A Fast Multi-objective Harmony Search Algorithm for Two-locus Model Detection in GWAS

Abstract: Background:: Genome-Wide Association Study (GWAS) plays a very important role in identifying the causes of a disease. Because most of the existing methods for genetic-interaction detection in GWAS are designed for a single-correlation model, their performances vary considerably for different disease models. These methods usually have high computation cost and low accuracy. Method:: We present a new multi-objective heuristic optimization methodology named HSMMGKG for detecting genetic interactions. In HS-MMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The computation complexity seems to be very high, but most of the operations are Boolean logic operations, so the speed is very fast. The speed improvement of the storage structure and Boolean operation has been proved in other studies [29], [30], [33].…”
Section: The Boolean Representation and Operation Of Gwas Datamentioning
confidence: 69%
See 2 more Smart Citations
“…The computation complexity seems to be very high, but most of the operations are Boolean logic operations, so the speed is very fast. The speed improvement of the storage structure and Boolean operation has been proved in other studies [29], [30], [33].…”
Section: The Boolean Representation and Operation Of Gwas Datamentioning
confidence: 69%
“…In this work, we compared SHEIB-AGM with six other methods, DECMDR [22], SNPHarvester [24], MACOED [25], AntEpiSeeker [26], HS-MMGKG [29] and SEE [30], on three simulated datasets. All seven software packages and their parameter settings are shown in Table 1.…”
Section: A Experiments On Simulated Data 1) Simulated Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, quality control was conducted on 1980 severe COVID-19 patients, and 1,610 patients remained after removing population outliers. Then, the researchers performed a GWAS on 835 Italian patients and 1,255 control group members ( Sun et al, 2019 ), as well as 775 Spanish patients and 950 control group members. As a result, they obtained severe COVID-19 risk data for 8,582,968 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…The Genome-wide association study (GWAS) is an observational study that detects the single nucleotide polymorphisms (SNP) of multiple individuals of a specific species to find genetic variations associated with a particular trait ( Li et al, 2015 ; Liu and Jiang, 2016 ; Jiang et al, 2017 ; Bush, 2019 ; Cheng et al, 2019b ; Sun et al, 2019 ). In recent years, there have been many studies that have identified several risk genes associated with gingivitis through the GWAS analysis.…”
Section: Introductionmentioning
confidence: 99%